Association of Microvascular Function and Endothelial Biomarkers With Clinical Outcome in Dengue: An Observational Study - Simmons, Cameron (2018)
BACKGROUND: The hallmark of severe dengue is increased microvascular permeability, but alterations in the microcirculation and their evolution over the course of dengue are unknown. METHODS: We conducted a prospective observational study to evaluate the sublingual microcirculation using side-stream dark-field imaging in patients presenting early (<72 hours after fever onset) and patients hospitalized with warning signs or severe dengue in Vietnam. Clinical findings, microvascular function, global hemodynamics assessed with echocardiography, and serological markers of endothelial activation were determined at 4 time points. RESULTS: A total of 165 patients were enrolled. No difference was found between the microcirculatory parameters comparing dengue with other febrile illnesses. The proportion of perfused vessels (PPV) and the mean flow index (MFI) were lower in patients with dengue with plasma than those without leakage (PPV, 88.1% vs 90.6% [P = .01]; MFI, 2.1 vs 2.4 [P = .007]), most markedly during the critical phase. PPV and MFI were correlated with the endothelial activation markers vascular cell adhesion molecule 1 (P < .001 for both) and angiopoietin 2 (P < .001 for both), negatively correlated. CONCLUSIONS: Modest microcirculatory alterations occur in dengue, are associated with plasma leakage, and are correlate with molecules of endothelial activation, angiopoietin 2 and vascular cell adhesion molecule 1.